UNDERSTANDING THE IMAGE OF PRINCE PROSPERO IN “THE MASK OF THE RED DEATH” - Pulatova, Sabina Sharifovna; Temirov, Khayrullo Tulkinovich (Educational Research in Universal Sciences, 2023)
This article is devoted to the study of the Edgar Allan Poe’s short story “The Mask of the Red Death”. It mainly focuses on the analysis of positive and negative features of ideal and negligent ruler in the given literary piece. The story serves as an allegory for the inevitability and inescapability of the death, emphasizing that no amount of wealth or power can protect against its reach. These concepts are fully explained with the help of extracts taken from the literary work.